Anemone bleaching increases the metabolic demands of symbiont anemonefish - Norin, Tommy (2020)
Increased ocean temperatures are causing mass bleaching of anemones and corals in the tropics worldwide. While such heat-induced loss of algal symbionts (zooxanthellae) directly affects anemones and corals physiologically, this damage may also cascade on to other animal symbionts. Metabolic rate is an integrative physiological trait shown to relate to various aspects of organismal performance, behaviour and locomotor capacity, and also shows plasticity during exposure to acute and chronic stressors. As climate warming is expected to affect the physiology, behaviour and life history of animals, including ectotherms such as fish, we measured if residing in bleached versus unbleached sea anemones (Heteractis magnifica) affected the standard (i.e. baseline) metabolic rate and behaviour (activity) of juvenile orange-fin anemonefish (Amphiprion chrysopterus). Metabolic rate was estimated from rates of oxygen uptake [Formula: see text], and the standard metabolic rate [Formula: see text] of anemonefish from bleached anemones was significantly higher by 8.2% compared with that of fish residing in unbleached anemones, possibly due to increased stress levels. Activity levels did not differ between fish from bleached and unbleached anemones. As [Formula: see text] reflects the minimum cost of living, the increased metabolic demands may contribute to the negative impacts of bleaching on important anemonefish life history and fitness traits observed previously (e.g. reduced spawning frequency and lower fecundity).